2018
DOI: 10.1016/j.peptides.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin modulates pain sensitivity of CFLP mice

Abstract: Kisspeptin, a hypothalamic neuropeptide, is a member of the RF-amide family, which have been known to modify pain sensitivity in rodents. The aim of the present study was to investigate the effect of kisspeptin-13 (KP-13), an endogenous derivative of kisspeptin, on nociception in adult male and female CFLP mice and the possible interaction of KP-13 with morphine on nociception. Mice were injected with different doses of KP-13, 30, 60 and 120 min after of which the nociceptive sensitivity were assessed via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…It has been discovered that kisspeptin attenuates morphine effect [28], and is expressed in the NAc [44], pointing to its possible involvement in the regulation of mesocorticolimbic dopaminergic activity. Interestingly, the centers of reward and addiction have also been implicated in the regulation of locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been discovered that kisspeptin attenuates morphine effect [28], and is expressed in the NAc [44], pointing to its possible involvement in the regulation of mesocorticolimbic dopaminergic activity. Interestingly, the centers of reward and addiction have also been implicated in the regulation of locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that central administration of kisspeptin-13 to rodents causes nociceptive effects (Spampinato et al 2011;Elhabazi et al 2013;Csabafi et al 2018). The activation of KISS1R has been shown to result in calcium mobilization and recruitment of mitogen-activated protein kinases (MAPKs) such as the extracellular signal-regulated kinases (ERK) and p38 (Castano et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental trials were conducted on the climatic chamber with 6 individuals at a time, and the bats were assigned to only one period and dose treatments. The range of LPS doses represent the maximum dose used in previous studies with bats (5 mg/kg LPS - Stockmaier et al 2015; 2018) and doses at least two to three times that value.…”
Section: Methodsmentioning
confidence: 99%
“…Three-way mixed ANOVA (2 Between subject factors / 1Within subject factor) were used to test for the interaction effects of dose (PBS, 5 mg/kg LPS, 10 mg/kg LPS, and 15 mg/kg LPS) and time of injection (resting or activity) as between subject factors, and time (ΔTb for 12 hours) as within subject factors on skin temperature change (ΔTb). When three-way interaction or two-way interaction were significant, simple main effect of factors (dose, time of injections and time) were tested by a Bonferroni post-hoc test for pairwise means comparisons (Rygula et al 2006; Csabafi et al 2018; Cohen et al 2020; Guan et al 2020; Sun et al 2021). Main effect Three-way mixed ANOVA were interpreted in the absence of statistically significant interactions (Maxwell and Delaney 2004; Kiernan 2014) by Tukey HSD or Bonferroni post-hoc test for pairwise comparisons when applicable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation